2001
DOI: 10.1159/000048701
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Choline Availability Alters the Localization of p15Ink4B and p27Kip1 Cyclin-Dependent Kinase Inhibitors in the Developing Fetal Rat Brain Hippocampus

Abstract: Previously we have shown that changes in maternal dietary choline are associated with permanent behavioral changes in offspring. Importantly, in adult male rats, feeding a choline-deficient diet increases the localization of cyclin-dependent kinase inhibitors (CDKIs) in the liver, whereas young adult CDKI knockout mice (p15Ink4B or p27Kip1) exhibit behavioral abnormalities. Thus, maternal dietary choline-CDKI interactions could underlie the changes we observe in fetal hippocampal development and cognitive func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…Surprisingly, netrin-1 and DCC showed similar changes in the CD and CS groups. This is in contrast to mitotic inhibition, apoptosis, and cell proliferation in fetal developing hippocampus which do not track in the same direction in the CD and CS groups [2][3][4]7,14], suggesting not only that each of these components of neurogenesis has a different choline dose-response, but also that the consequences of netrin-DCC signaling for precursor cell migration are dependent on additional molecular interactions. For example, recent reports suggest a critical role for cyclic nucleotides in regulating the response to guidance cues.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Surprisingly, netrin-1 and DCC showed similar changes in the CD and CS groups. This is in contrast to mitotic inhibition, apoptosis, and cell proliferation in fetal developing hippocampus which do not track in the same direction in the CD and CS groups [2][3][4]7,14], suggesting not only that each of these components of neurogenesis has a different choline dose-response, but also that the consequences of netrin-DCC signaling for precursor cell migration are dependent on additional molecular interactions. For example, recent reports suggest a critical role for cyclic nucleotides in regulating the response to guidance cues.…”
Section: Introductionmentioning
confidence: 94%
“…We previously showed that, depending on the availability of maternal dietary choline, precursor cells in ventricular zone undergo proliferation and commit to differentiate into neuronal cell types (e.g., calretinin-containing cells) [8] known to regulate memory, or undergo apoptosis. We previously described how choline availability affects pro-apoptotic signal transduction in neuronal-type cells [18,28] and hepatocytes [1,4,6,7,9]. We are beginning to understand how maternal dietary choline availability during pregnancy affects not only the generation, but also the targeted migration of precursor neuronal-type cells in the fetal hippocampus [2,3,14].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Intrauterine choline deficiency has been shown to result in structural defects in the hippocampus of rats [36] and mice [37][38][39]. Choline availability altered the timing, genesis, migration and differentiation of progenitor neuronal-type cells in the fetal hippocampus.…”
Section: Betaine Supplementation To Lactating Dams Increases Betaine mentioning
confidence: 99%